(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Field work has an important role to play in developing geographical interest in the students of geography. For most geographies the importance and significance of field work needs no reinforcement and is a key component of their own personal biographies in the subject. In the syllabus of secondary classes under West Bengal board of secondary education scope might have limited of the learners to acquire knowledge through field work consequently. Overall, the study seeks to asses to relationship between achievement in geography in secondary level under West Bengal board of secondary education through traditional method and field work method of teaching.